(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study investigatesboth the impact of participation in the National Fitness 100 project, a National Sports Promotion Act of Korea policy, and plans for implementing operational efficiencies. It highlights the significance of the project and provides information to help people at home and abroad live healthy lives by improving their fitness. The research participants were three exercise therapists and one physical-fitness tester,selected from regional physical-fitness centers in four South Korean cities (C, D, J, N), as well as four people who have participated in National Fitness 100 every year since 2017. In-depth interview data were collected and analyzed in depth through an inductive category analysis. The first impact of participation in National Fitness 100 was participant satisfaction with sports programs accessed through free fitness tests and personalized exercise prescriptions; these were recognized as a state-supported sports-welfare service. Second, the state-approved fitness certificate issued for eachfitness-certification stage gave participants pride and a sense of challenge, motivating them to continue to engage withNational Fitness 100. To ensure thatNational Fitness 100 operates efficiently, it is essential, first, to develop certificates that evaluate and recognize the individual goals achieved by participants. Second, the recently introduced Sports Activity Certification service should improve participation through active promotion and compensation systems, based on records of sports-activity performance. Third, health, nutrition, hygiene, and fitness must be integrated through governance activation to enable collaboration and improvement among disadvantaged groups and regions. Finally, it is expected that this study will provide information and practice to improve health and fitness, which havebeen impeded by the spread of COVID-19 worldwide.